A highly selective aggregation‐induced emission fluorogen for sensitive detection of Al3+ in living cells. (10th September 2019) - Xie, Ya; Li, Xueming; Yan, Liqiang; Li, Jianping
Abstract: A Schiff's base derivative was synthesized using a condensation reaction between 8‐formyl‐7‐hydroxy‐4‐methylcoumarin and furan‐2‐carbohydrazide that produced marked aggregation‐induced emission and had excellent ability to specifically recognize aluminium ions (Al 3+ ). This compound displayed faint fluorescence in the benign solvent dimethyl formamide, and exhibited obvious green fluorescence following addition of specific amounts of water. Moreover, it exhibited strong blue fluorescence after combination with Al 3+ even in the presence of other interfering ions. These experimental results demonstrated that this derivative could be used as a fluorescence probe for Al 3+ . The advantages, including significant fluorescence change, high selectivity and sensitivity, and fast response, meant that this probe could be used both to detect Al 3+ in water samples and for fluorescence imaging in living cells.